Navigating Genetic Testing in Nephrology: Options and Decision-Making Strategies - Emily Groopman; Hila Milo Rasouly (Kidney International Reports)
Technological advances such as next-generation sequencing (NGS) have enabled high-throughput assessment of the human genome, supporting the usage of genetic testing as a first-line tool across clinical medicine. Although individually rare, genetic causes account for end-stage renal disease in 10% to 15% of adults and 70% of children, and in many of these individuals, genetic testing can identify a specific etiology and meaningfully impact management. However, with numerous options for genetic testing available, nephrologists may feel uncomfortable integrating genetics into their clinical practice. Here, we aim to demystify the process of genetic test selection and highlight the opportunities for interdisciplinary collaboration between nephrologists and genetics professionals, thereby supporting precision medicine for patients with kidney disease. We first detail the various clinical genetic testing modalities, highlighting their technical advantages and limitations, and then discuss indications for their usage. Next, we provide a generalized workflow for genetic test selection among individuals with kidney disease and illustrate how this workflow can be applied to genetic test selection across diverse clinical contexts. We then discuss key areas related to the usage of genetic testing in clinical nephrology that merit further research and approaches to investigate them.